1989
DOI: 10.1128/jb.171.3.1772-1774.1989
|View full text |Cite
|
Sign up to set email alerts
|

13N isotope studies of glutamine assimilation pathways in Neurospora crassa

Abstract: L-[amide-'3N]glutamine in Neurospora crassa is metabolized to [13N]glutamate by glutamate synthase and to [13N]ammonium by the glutamine transamina-w-amidase pathway. The [13Njammonium relased is assimilated by glutamate dehydrogenase and glutamine synthetase, confirming the operation of a glutamine cycle. Most of the nitrogen is retained during cycling between glutamate and glutamine.In Neurospora crassa, glutamine, in addition to participating in transamidation reactions, is converted to 2-oxoglutarate and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This metabolic adjustment in reducing the cycling of glutamine results in similar growth of the parental and the a-me-MSO-resistant mutant strains in low ammonia. These data point out that an excess of GS activity ensures a higher glutamine cycling, something that allows for a wider range adjustment in the glutamate/glutamine ratio, which is also in accordance with the proposal that the function of GOGAT in N. crassa is to recycle glutamine to glutamate (1,3,15).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…This metabolic adjustment in reducing the cycling of glutamine results in similar growth of the parental and the a-me-MSO-resistant mutant strains in low ammonia. These data point out that an excess of GS activity ensures a higher glutamine cycling, something that allows for a wider range adjustment in the glutamate/glutamine ratio, which is also in accordance with the proposal that the function of GOGAT in N. crassa is to recycle glutamine to glutamate (1,3,15).…”
supporting
confidence: 66%
“…It has been found that GS is involved in glutamine cycling, in which this amino acid is continually assimilated by GOGAT, degraded by the glutamine transaminase-wamidase pathway, and resynthesized (1)(2)(3)(4). It has been proposed that this cycle is necessary for carbon utilization (11).…”
mentioning
confidence: 99%
“…1) is consistent with, but does not prove, the possibility that glutamine is the source of this NH,. Glutaminase activity has been shown to be present (Chase and Kankel, 19871, but other routes of glutamine breakdown or cycling which do not release free NH, exist in other systems (see e.g., Calderon et al, 1989;Haussinger et al, 1985) and remain uninvestigated possibilities.…”
Section: Ammonia Production and Hsp Expressionmentioning
confidence: 99%
“…glutamine have demonstrated that the glutamine cycle operates during growth of wild-type N. crassa and have given information about the rate and amount of nitrogen cycling (6). After the addition of L-[amide-13N]glutamine to the wild-type strain, glutamate was more highly labeled than other nitrogen-containing metabolites.…”
Section: Recent Experiments On the Distribution Of L-[amide-13n]mentioning
confidence: 99%